EVALUASI SISTEM PENGUKURAN KINERJA (STUDI DI DINAS BANGUNAN GEDUNG DAN ASET DAERAH KOTA YOGYAKARTA) - , Meizanti Listiyani Z; , Dr. Rusdi Akbar, M.Sc., CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Accountability is derived from Presidential Instruction No. 7 of 1999 on Government Performance Accountability (AKIP) which mandates the existence of an obligation of a government agency accountable for its performance and report to the parties that represent the right or the authorized one to request for responsibility. Performance Blueprint approach (performance blueprint) can be used to measure the quality of compiled performance indicators and reported by the city of Yogyakarta by using two tools, which are logic models and four quadrant analysis. The research method is done by analysing the data and confirm ing it by interview. These results indicate that the performance measurement conducted by the Department of Regional Building and Assets in accordance with existing regulations on Ministry of Administrative Reform and Bureaucratic Reformâs Regulation No. 29 of 2010, but still there is a lack of information suitability contained in planning and reporting documents, performance indicators used by DBGAD there are indicators that do not fit between planning and reporting documents. Besides, DBGAD performance indicators still lies in quadrant 3, not quadrant 4 yet.